2007
DOI: 10.1042/bst0350442
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicron remnants: mediators of endothelial dysfunction?

Abstract: Vascular disease is initiated by activation of the endothelium characterized by the predominance of pro-inflammatory and pro-coagulant changes in endothelial cells (ECs) referred to collectively as 'endothelial dysfunction'. There is increasing evidence that lipoproteins of dietary origin modulate EC function and the use of artificial chylomicron remnant-like particles (CRLPs) in vitro is now beginning to shed light on the molecular mechanisms through which these particles influence cell behaviour. CRLPs enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This process results in TGRL remnant particle formation and lipolysis products such as phospholipids and fatty acids. Previous studies have shown that TGRL lipolysis products cause aortic endothelial injury, including inflammation, elevated expression of reactive oxygen species (ROS), and increased vascular permeability (22)(23)(24)(25)(26)(27)(28)(29). Additionally, activating transcription factor (ATF) 3 appears to play an important role as a master regulator of inflammation in the aortic endothelium in response to TGRL lipolysis products (22,30).…”
Section: Electron Paramagnetic Resonance Spin Trapping Of Superoxide mentioning
confidence: 99%
“…This process results in TGRL remnant particle formation and lipolysis products such as phospholipids and fatty acids. Previous studies have shown that TGRL lipolysis products cause aortic endothelial injury, including inflammation, elevated expression of reactive oxygen species (ROS), and increased vascular permeability (22)(23)(24)(25)(26)(27)(28)(29). Additionally, activating transcription factor (ATF) 3 appears to play an important role as a master regulator of inflammation in the aortic endothelium in response to TGRL lipolysis products (22,30).…”
Section: Electron Paramagnetic Resonance Spin Trapping Of Superoxide mentioning
confidence: 99%
“…This reduction of FMD correlated with TG and FFA concentrations and was reversible when TG concentrations decreased at the end of the oral fat loading test [57]. Furthermore, postprandial TRLs have been shown to induce the expression of leukocyte adhesion molecules on the endothelium, facilitating recruitment of inflammatory cells [59] and remnant lipoproteins have been found to activate endothelial cells by upregulating COX-2 expression and activating intracellular signaling pathways controlled by nuclear factor-kappaB and mitogen-activated protein kinases [60]. …”
Section: Postprandial Lipemia and Vascular Integritymentioning
confidence: 99%
“…Remnant TAG-rich lipoproteins isolated from hyperlipidaemic subjects impaired endothelium-dependent relaxation in rabbit aortic strips ( 154 ) and levels of remnant TAG-rich lipoproteins were associated with impaired dilation of coronary arteries in human subjects, linked to NO bioavailability ( 155 ) . Some recent research using artificial chylomicron remnant-like particles has helped to resolve the molecular mechanisms that mediate postprandial effects on the endothelium, showing that these particles inhibit NO production from cultured endothelial cells, induce cyclo-oxygenase-2 activity, and increase expression of inflammatory molecules and antioxidant enzymes ( 156 ) .…”
Section: Dietary Fat and Vascular Functionmentioning
confidence: 99%